AN ANALYSIS OF THE IMPACT OF CONFIDENCE ON THE RELIABILITY OF EARTHQUAKE DETECTION UNDERGROUND - Mukhtorov, Sherzod Sobirjon ugli; Rustamova, Muhlisa Muxtaraliyevna (Educational Research in Universal Sciences, 2022)
The problem of ensuring high reliability of utilization and treatment of wastewater from the population is currently relevant in connection with the rapid growth of water consumption and, consequently, the increase in the volume of wastewater. Sewage networks play an important role in solving the problem of ensuring the reliability of the sewage system. Particular attention should be paid to the reliability of drainage networks in areas prone to seismic impact, as in some cases accidents in them cause more damage than earthquakes themselves. In areas prone to seismic impact, special attention should be paid to the reliability of drainage networks, as in some cases accidents in them cause more damage than earthquakes themselves.Therefore, seismic zones are taken into account in the process of laying the networks.